Antiplatelet treatment for acute secondary prevention of non-cardioembolic minor stroke / transient ischaemic attack: an update for the acute physician. Issue 5 (2022) - Krishnan, Kailash; Law, Zhe Kang; Minhas, Jatinder S; Bath, Philip M; Robinson, Thompson G; Sprigg, Nikola
No abstract available